Motivators and Inhibitors of Implementing Sustainable Hospitality Supply Chain Management - Xu, X.; Gursoy, D (Emerald Group Publishing Limited, 2015)
Purpose: To examine the motivators and inhibitors for hospitality businesses to implement sustainable hospitality supply chain management. Methodology/approach: Based on a framework of hospitality supply chain and following the principles of triple bottom line reporting (3BL) approach, this chapter discusses the motivaors and inhibitors for hospitality businesses to implement sustainable hospitality supply chain management. Findings: Both the internal motivators such as financial benefits and external motivators such as stakeholders’ pressure encourage hospitality businesses’ sustainability practices. However, inhibitors such as managers’ attitudes, budget limitations, and conflicts among different stakeholders are likely to have negative impacts on sustainability efforts. Originality/value of paper: This chapter emphasizes the importance of cooperation and coordination among the stakeholders for a succcessful implementation of a hospitality supply chain.